Seasonal variation and threat assessment of bird diversity at Gajedi Wetland, Rupandehi, Nepal - Regmi, Sovit Raj; Jha, Praveen Kumar; Gyawali, Seejan (Nepalese Journal of Zoology, 2023)
Wetlands provide important breeding, feeding, and resting habitats that support bird species; however, these wetlands are under anthropogenic pressure. This study aimed to record the diversity of birds and identify the major threats to them. The study was conducted in Gajedi Wetland, Rupandehi, Nepal. The point count method was used, where six vantage points separated by 300 m were taken. The observation was carried out from October 2022 to January 2023 using direct observation and call record methods. We recorded 1067 individual birds of 84 species under 61 genera belonging to 38 families of 16 orders. Out of 84 species, 67 were residents, 16 were winter migrants, and one was summer migrant. Shannon-Wiener function, Simpson’s diversity index and Margalef’s Richness Index were higher in winter, compared to autumn. However, Pielou’s evenness index was greater in the autumn season than in the winter season. The rose-ringed parakeet (Psittacula krameria) was the most abundant species. We observed eight nationally threatened, one globally threatened, two globally near-threatened species and five species listed under Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Recreational activities were among the major threats to birds in Gajedi Wetland. We recommend a complete survey including all season to produce a more comprehensive checklist and reduce anthropogenic activities around the wetland.